Care of the critically ill patient. Issue 4 (April 2018) - Cairns, Thomas; Faulds, Matthew
Abstract: Modern intensive care medicine requires a multidisciplinary approach to look after critically ill patients. Dedicated critical care units offer a variety of facilities to monitor and support organ functions, allowing diagnosis and treatment of life-threatening conditions in a controlled environment. This article describes the main principles of intensive care medicine, giving an overview of a systematic approach to assessment and treatment of organ dysfunction, and highlights some of the complex ethical and organizational challenges.